Sustaining hope as a moral competency in the context of aggressive care. (November 2015) - Peter, Elizabeth; Mohammed, Shan; Simmonds, Anne
Background: Nurses who provide aggressive care often experience the ethical challenge of needing to preserve the hope of seriously ill patients and their families without providing false hope. Research objectives: The purpose of this inquiry was to explore nurses' moral competence related to fostering hope in patients and their families within the context of aggressive technological care. A secondary purpose was to understand how this competence is shaped by the social–moral space of nurses' work in order to capture how competencies may reflect an adaptation to a less than ideal work environment. Research design: A critical qualitative approach was used. Participants: Fifteen graduate nursing students from various practice areas participated. Ethical considerations: After receiving ethics approval from the university, signed informed consent was obtained from participants before they were interviewed. Findings: One overarching theme 'Mediating the tension between providing false hope and destroying hope within biomedicine' along with three subthemes, including 'Reimagining hopeful possibilities', 'Exercising caution within the social–moral space of nursing' and 'Maintaining nurses' own hope', was identified, which represents specific aspects of this moral competency. Discussion: This competency represents a complex, nuanced and multi-layered set of skills in which nurses must be well attuned to the needs and emotions of their patients and families, have the foresight to imagine possible future hopes, be able to acknowledge death, have advanced interpersonal skills, maintain their own hope and ideally have the capacity to challenge those around them when the provision of aggressive care is a form of providing false hope. Conclusion: The articulation of moral competencies may support the development of nursing ethics curricula to prepare future nurses in a way that is sensitive to the characteristics of actual practice settings.